Depression and changes in educational attainment using administrative data: The role of socio-demographic characteristics - Wickersham, Alice; Dickson, Hannah; Stewart, Robert; Ford, Tamsin; Downs, Johnny (International Journal of Population Data Science, 2019)
Background Research has shown depression to result in poorer educational attainment among children. However, comparatively little is known about the relationship between depression and attainment over time, and the role that children’s socio-demographic characteristics might play. Aim To describe the educational attainment trajectory profiles of children with a clinical diagnosis of depression, and to explore whether these trajectory profiles vary by gender, ethnicity, area-level deprivation and age at diagnosis. Methods This is a historical, longitudinal cohort study, making use of two linked administrative datasets. First, a cohort of children (<18 years) were identified who had received a first diagnosis of depression from the South London and Maudsley NHS Foundation Trust between 2007 and 2013 (n=1490). Their pseudonymised secondary mental healthcare records were extracted via the Clinical Record Interactive Search application at the Trust’s Biomedical Research Centre. These records were then linked to England’s National Pupil Database, which contains attainment data for these children at three timepoints of interest: Key Stage 1 (ages 5 to 7 years), Key Stage 2 (7 to 11 years) and Key Stage 4 (14 to 16 years). Longitudinal mixed models for repeated measures will be conducted to model changes in attainment over these three timepoints according to gender, ethnicity, area-level deprivation and age at diagnosis. Results Preliminary results are suggestive of attainment trajectories in this cohort varying according to their socio-demographic characteristics. Analysis will be completed August 2019. Conclusion The findings from this study will identify whether some groups of depressed children experience better or worse patterns of educational attainment over time. This could highlight priorities for intervention in England’s ongoing efforts to improve child mental health provision in schools.